The Influence of Digital Comics Silat Sliwa Betawi on Cultural Literacy in Teenagers Bulak Simpul Kalideres - Syakura, Amanda Rizky; Kurnianingsih, Indah; Erza, Elfitri Kurnia (Edulib, 2021)
Cultural literacy is the ability to know, recognize and understand the culture that exists in an environment.  Preserving a culture must be so as not to disappear or become extinct, one of the cultures that need help  developing is Silat Sliwa Betawi in Kalideres. This research aims to analyze the influence of silat Sliwa Betawi  digital comics on cultural literacy in the teenager Bulak Simpul Kalideres.This type of research is a  combination of research with experimental research. The subject of the study was a teenager in Bulak  Simpul Kalideres, while the object of this study was the influence of Silat Sliwa Digital Comics on Cultural  Literacy in Bulak Simpul, Kalideres. The final sample count used for the analysis was 36 adolescents.  Running the research site in Bulak Simpul Kalideres. Data collection techniques use active participation  observations, unstructured interviews, and questionnaires. It runs the data analysis into two stages:  qualitative data analysis and quantitative data analysis. After conducting pre-test, experiments with digital  comics, post-test then analyze the last data using the Wilcoxon Signed Rank Test method, which gets the  result that the value of Pvalue = 0.000 is smaller than α=5%, where if Pvalue is smaller than α then there is a  significant influence between after and before the treatment of the use of Sliwa Betawi digital comics on  cultural literacy.